2014
DOI: 10.1098/rspb.2013.3096
|View full text |Cite
|
Sign up to set email alerts
|

Food sharing is linked to urinary oxytocin levels and bonding in related and unrelated wild chimpanzees

Abstract: Humans excel in cooperative exchanges between unrelated individuals. Although this trait is fundamental to the success of our species, its evolution and mechanisms are poorly understood. Other social mammals also build long-term cooperative relationships between non-kin, and recent evidence shows that oxytocin, a hormone involved in parent-offspring bonding, is likely to facilitate non-kin as well as kin bonds. In a population of wild chimpanzees, we measured urinary oxytocin levels following a rare cooperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
200
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(212 citation statements)
references
References 83 publications
(195 reference statements)
7
200
2
3
Order By: Relevance
“…However, if the prosocial option were only used to motivate future assistance, subjects' behaviors should have been the same in the RA and NRA conditions in experiment 3. A more probable explanation is instead that chimpanzees' choices were mediated by affiliative reactions in response to their partner's cooperative efforts; this would correspond to theoretical accounts suggesting that chimpanzees may engage in some form of "emotional bookkeeping" such that individuals make social decisions based on emotional states associated with particular partners (14, 51, 52), which may also be consistent with empirical findings showing that chimpanzees show elevated oxytocin levels-a hormone involved in social bonding-in response to cooperative interactions (48,53), and this may mediate individuals' propensity to engage in cooperative activities with particular partners in the future. Hence, in the current experiments, subjects may have interpreted the partner's assistance (and thus her decision to deviate from a payoff-maximizing strategy) as an invitation to contribute to a mutually desirable cooperative outcome (54), triggering positive affect toward the partner and motivating reciprocation.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, if the prosocial option were only used to motivate future assistance, subjects' behaviors should have been the same in the RA and NRA conditions in experiment 3. A more probable explanation is instead that chimpanzees' choices were mediated by affiliative reactions in response to their partner's cooperative efforts; this would correspond to theoretical accounts suggesting that chimpanzees may engage in some form of "emotional bookkeeping" such that individuals make social decisions based on emotional states associated with particular partners (14, 51, 52), which may also be consistent with empirical findings showing that chimpanzees show elevated oxytocin levels-a hormone involved in social bonding-in response to cooperative interactions (48,53), and this may mediate individuals' propensity to engage in cooperative activities with particular partners in the future. Hence, in the current experiments, subjects may have interpreted the partner's assistance (and thus her decision to deviate from a payoff-maximizing strategy) as an invitation to contribute to a mutually desirable cooperative outcome (54), triggering positive affect toward the partner and motivating reciprocation.…”
Section: Discussionsupporting
confidence: 71%
“…Given the careful counterbalancing scheme and as indicated by the session and trial number analysis, our findings cannot be explained by local enhancement, order effects, or learning. Moreover, previous research has demonstrated the importance of stable social bonds in primate cooperation (48)(49)(50). In the current experiments, however, increases in prosocial choices after receiving risky assistance were highly consistent across subjects who differed in rank and their social relationship with the partner (Table S2).…”
Section: Discussioncontrasting
confidence: 42%
“…Evidently, grooming with a close friend or relative is more emotionally rewarding than engaging in the same behaviour with a less preferred partner. Chimpanzees also exhibit elevated OT levels after sharing food [113]. In healthy humans, inhaling OT, which translocates the peptide into the brain, increases trust and prosocial behaviour [114,115].…”
Section: Neuromodulatory Sources Of Variation In Cooperative Potentialmentioning
confidence: 99%
“…We conducted focal animal sampling (23) for 20 adult male and female chimpanzees of two neighboring groups, and measured the oxytocin concentration of urine samples from all individuals using an established method to sample specific events (19,20).…”
mentioning
confidence: 99%
“…These parallels highlight key features shared by chimpanzee and human group defense and intergroup conflict (14). Also similar to humans, the oxytocinergic system in chimpanzees is involved in prosocial and cooperative behavior between both kin and nonkin group members, such as grooming (19) and food sharing (20), suggesting parallels in oxytocinergic system involvement between humans and chimpanzees.…”
mentioning
confidence: 99%